Regularized Kelvinlet Inversion for Real-Time Image Deformation and Video Time Warping - Haetinger, Guilherme Gomes; Gastal, Eduardo S. L. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
We present a novel approach for image deformation and video time warping. Our technique involves the inversion of the nonlinear regularized Kelvinlet equations, leading to higher-quality results and time/space efficiency compared to naive solutions. Inversion is performed by a per-pixel optimization process, being inherently parallel and achieving real-time performance in Full HD videos (over 300 fps). We demonstrate our method on a variety of images and videos, in addition to discussing some important technical and theoretical details.